2008
DOI: 10.1007/s10461-008-9365-5
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Among HIV Positive and Negative Prevention of Mother to Child Transmission (PMTCT) Clients in a Resource Poor Setting in South Africa

Abstract: The purpose of this study was to investigate family planning needs, knowledge of HIV transmission and HIV disclosure in a cohort sample that had undergone PMTCT in a resource poor setting. Five public clinics implementing PMTCT from Qaukeni Local Service Area, O.R. Tambo District in the Eastern Cape. The sample at postnatal care consisted of 758 women with known HIV status. From 116 HIV positive women 76.3% and from 642 HIV negative women 85.2% got counseling on safe sex during pregnancy but only 65.8% and 62.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
66
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 20 publications
12
66
0
Order By: Relevance
“…This has been reported in a study among HIV positive and negative PMTCT clients in a South Africa where having fewer children was associated with greater pregnancy desire among the HIV negative women (Peltzer et al, 2009). Additionally, a study among HIV positive and negative women in the national PMTCT program in Rwanda found women with fewer children had a stronger desire for additional children (Hoffman et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
“…This has been reported in a study among HIV positive and negative PMTCT clients in a South Africa where having fewer children was associated with greater pregnancy desire among the HIV negative women (Peltzer et al, 2009). Additionally, a study among HIV positive and negative women in the national PMTCT program in Rwanda found women with fewer children had a stronger desire for additional children (Hoffman et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
“…6 The HIV epidemic is having a profound and complex effect on reproductive behavior in Africa. A desire for fewer children among HIV-positive women than among HIV-negative women or women of unknown status has been documented both in cross-sectional studies [7][8][9][10][11][12] and in longitudinal studies that followed women after they received their HIV diagnosis. [13][14][15][16] Women's decreased desire for additional children after learning they are HIVpositive has been explained by concerns over motherto-child transmission and leaving orphans, as well as by perceived health risks involved in pregnancy for an HIVpositive woman.…”
mentioning
confidence: 99%
“…Although this was the case in some studies, 9,18 others found that contraceptive use was similar or lower among HIV-positive women than among their HIVnegative counterparts. 12,19 Contraceptive decisions add another dimension to reproductive choices-HIV-positive women have to navigate specific risks related to their status, such as potential interactions between contraceptives, HIV and antiretroviral drugs, or having to explain the need for contraception to a partner. 8 Considerations of abortion further complicate reproductive decisions for HIV-positive women in Africa, as they must weigh the often heavy stigma and high risk associated with a clandestine abortion against the stigma of continuing a pregnancy while HIVpositive.…”
mentioning
confidence: 99%
“…Various studies acknowledge the desire of PLHIV to have children (Nattabi et al, 2009). Among HIV-positive women at clinics in the Eastern Cape (South Africa) 38.8% expressed a pregnancy desire and only 65.8% reported condom use (Peltzer et al, 2009). Oladapo et al (2005) reported that in a suburban clinic in Nigeria 71.5% men and 93.3% women living with HIV wanted children.…”
Section: Introductionmentioning
confidence: 99%